Production of graphene-boron nitride hybrid nanosheets by liquid-phase exfoliation - Guler, Omer; Guler, Seval Hale (Elsevier Gmbh, 2016)
Hexagonal graphite (HG) and hexagonal boron nitride (h-BN) show various characteristics that are different from each other in addition to their similar features. It is thought that hybrid nanosheets which are formed of nano-layered graphene and nano-layered boron nitride (BNNS) will show very extraordinary characteristics. In this study, the production of a new Hybrid structure containing graphene and BN nanosheet structures was performed by using the liquid-phase exfoliation method. For this purpose, as the starting material, HG and h-BN were mixed at the same ratio and added into an acid mixture and thus an intermediate structure called as Hybrid intercalated compound (HIC) was obtained. Then, the HIC structure obtained was subject to a thermal treatment and a structure called as expanded hybrid structure (EHS) was obtained. In order to produce a Hybrid nanosheet, the EHS structure was sonicated in dimethylformamide (DMF), which was used as a solvent. At the end of the treatment, the material floating in the solvent was filtered. The samples were subject to transmission electron microscope (TEM), scanning electron microscopy (SEM), atomic force microscope (AFM), Fourier transform infrared spectroscopy, and UV-vis spectroscopy examinations. As a result of the analyses, it was determined that the hybrid nanosheets containing graphene and BN nanosheets were successfully produced. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Graphene; BN nanosheet; Hybrid nanosheet; Liquid-phase exfoliation